Biblia w stylu rokoko. Malarstwo religijne w dobie kryzysu sztuki francuskiej - Niemira, Konrad (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article deal with religious paintings exhibited at the Salons of the Royal Academy of Painting and Sculpture in Paris from 1747 to 1748. In the late 1740s, a period often described as a time of crisis of French art and period of internal crisis of Royal Academy, specific mutation of this genre of art can be observed. My analysis is based on the strategies of three painters exhibiting their religious paintings at the Salon in 1747-1748: Jean Restout, Noël Hallé and François Boucher. In those examples the role that grand goût and rococo costume played in artistic and social culture of 1740s is presented.